PENERAPAN PENDIDIKAN KARAKTER MELALUI PROGRAM ADIWIYATA - Noprida Ilhamiah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
The growth of Indonesian development has increased so fast in every sector these few years. Furthermore, it creates environmental damage such as: pollutions, floods, erosion, forest fire, and etc. These problems are basically caused by the lack of society’s awareness to keep the environment clean. Based on these problems, Indonesian government through the State Minister for The Environment publish Adiwiyata program. The aim of these program is to introduce knowledge about character education especially in environmental care from elementary to senior high school students. It is hoped that the students will have such awareness to keep the environment clean earlier. The program of environmental education through Adiwiyata Program can be implemented in 2013 Curriculum through character education building. There are some characters education that can be implemented through Adiwiyata such as: care, discipline, responsibility, cooperation, and sincere.